Factors associated with time interval between the onset of symptoms and first medical visit in women with breast cancer - Ângela Ferreira Barros; Cristiane Murta-Nascimento; Carlos Henrique de Abdon; Daniela Nunes Nogueira; Emenny Line Cardoso Lopes; Adriano Dias
Women presenting with advanced breast cancer tumors are common in Brazil. Little is known about factors contributing to the delay in seeking care. The aim of this study was to identify factors associated with longer time intervals between the onset of breast cancer symptoms and the first medical visit in the Federal District, Brazil. The analysis included 444 symptomatic women with incident breast cancer, interviewed between September, 2012 and September, 2014, during their admission for breast cancer treatment in nine public hospitals in the Federal District. Patients with metastatic disease at diagnosis were not included in this study. The outcome was time interval between symptom onset and the first medical visit, whether > 90 (34% of patients) or ≤ 90 days. Logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (95%CI). In the multivariate analysis, the > 90 day interval was significantly associated with patients not performing mammography and/or breast ultrasound in the two years prior to breast cancer diagnosis (OR = 1.97; 95%CI: 1.26-3.08), and with more advanced stages (OR = 1.72; 95%CI: 1.10-2.72). Furthermore, there was a lower chance of delay in patients with higher levels of education (OR = 0.95; 95%CI: 0.91-0.99). A relatively high proportion of breast cancer patients in the Brazilian Federal District experienced delay to attend the first medical consultation after the symptoms onset. Increasing breast cancer awareness, especially among women with low educational levels and those not participating in mammography screening programs could contribute to reduce this delay.